2018
DOI: 10.31000/jgcs.v2i2.1027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Local Electoral Governance under Electoral Integrity Perspective in Yogyakarta City 2017

Abstract: The characteristic of a democratic country is implementation of election. In Indonesia it has include in national and local levels. Local elections held simultaneously in 2015, 2017 and 2018. One of the city conducting the election is Yogyakarta City. In the specifically this research explain about electoral governance in electoral integrity perspective. All stages of election which consists of pre-election, election period and post-election. This research use qualitative research method through interview and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Next up is (Riska Sarofah, Titin Purwaningsih, 2018) on the governance of local elections in the Election Integrity Perspective. The results of this study indicate that the governance of regional head elections in the city of Yogyakarta has integrity by the principles of electoral integrity applied at the stages of the implementation of regional head elections including pre-election, electoral process and post-election.…”
Section: Implementation Of Governance In Voting and Vote Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…Next up is (Riska Sarofah, Titin Purwaningsih, 2018) on the governance of local elections in the Election Integrity Perspective. The results of this study indicate that the governance of regional head elections in the city of Yogyakarta has integrity by the principles of electoral integrity applied at the stages of the implementation of regional head elections including pre-election, electoral process and post-election.…”
Section: Implementation Of Governance In Voting and Vote Countingmentioning
confidence: 99%
“…Furthermore, the results of (Nazir, 2017) research show that there are still many names, not registered in the permanent voter data, and those who have died are still registered on the permanent voter register. Furthermore, the results of (Riska Sarofah, Titin Purwaningsih, 2018) showed that in the voting process the coordination between the election organizers had not been maximized.…”
Section: Introductionmentioning
confidence: 99%
“…First is in the process of program planning and budget of election. Secondly process of socialization and voter information is carried out by taking into account the involvement of the community activities to make room for the district election committee and the commissioner in providing socialization Sarofah, et. al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hasil evaluasi menunjukkan bahwa dari segi proses, pilkada Walikota D.I. Yogyakarta pada tahun 2017 dapat dinilai sebagai pemilu berintegritas, ditandai dengan minimnya politik uang (Sarofah, Purwaningsih, & Nurhakim, 2019).…”
unclassified